The Effect of Institutional and Macro-Economic Variables on Share Prices of Listed Companies in Nepal - Phuldel, Anil; Dhital, Aagya; Bishwas, Anju; Timalsina, Bibek; Shrestha, Darbin; Pradhan, Radhe Shyam (Nepalese Journal of Business, 2025)
The study examines the effect of institutional and macro-economic variables on share prices of listed companies in Nepal. The dependent variables selected for the study are market price per share and market capitalization. The selected independent variables are earnings per share, dividend per share, price earnings ratio, GDP growth rate, interest rate and inflation rate. The study is based on secondary data of 12 commercial banks with 108 observations for the study period from 2014/15 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB), Economic Survey Report published by Ministry of Finance and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of institutional and macro-economic variables on share prices of Nepalese commercial banks. The study showed that earnings per share has a positive effect on market price per share and market capitalization. It means that increase in earnings per share leads to increase in market price per share and market capitalization. Similarly, dividend per share has a positive effect on market price per share and market capitalization. It means that increase in dividend per share leads to increase in market price per share and market capitalization. The results of the study also showed that price earnings ratio has a positive effect on market price per share and market capitalization. It implies that increase in price earnings ratio leads to increase in market price per share and market capitalization. Likewise, GDP growth rate has a positive effect on market price per share which indicates that higher GDP growth rate leads to increase in market price per share. However, interest rate has a negative effect on market price per share and market capitalization. It implies that higher interest rate leads to decrease in market price per share and market capitalization. Similarly, inflation rate has a positive effect on market price per share. It implies that higher inflation rate leads to increase in market price per share.